The Effect Of Education Level On Employee Performance At The Mandailing Natal Regency Environmental Agency - Nur Azizah Matondang; Abdi Sugiarto (Yayasan Multidimensi Kreatif, 2024)
This study aimed to analyze the effect of education level on employee performance at the Environmental Agency of Mandailing Natal Regency. This research was conducted using a quantitative associative causal approach. The sample consisted of all employees, totaling 71 people, selected through purposive sampling Based on the data analysis, the study found that education level had a positive and significant effect on employee performance. The hypothesis test results showed a t-value of 44.211, which was greater than the t-table value of 1.99495, with a significance level of 0.000, which was less than 0.05. The regression coefficient indicated that every one-unit increase in education level resulted in a 0.957-unit improvement in employee performance, assuming other variables remained constant. Additionally, the determination test results showed that education level explained 97% of the variability in employee performance, indicating a very high impact. The remaining 3% was influenced by other factors not examined in this study. Therefore, education level had a positive and significant effect on employee performance at the Environmental Agency of Mandailing Natal Regency.